2017
DOI: 10.1007/s10567-017-0226-5
|View full text |Cite
|
Sign up to set email alerts
|

Toward Creating Synergy Among Policy, Procedures, and Implementation of Evidence-Based Models in Child Welfare Systems: Two Case Examples

Abstract: Over the past four to five decades, multiple randomized controlled trials have verified that preventive interventions targeting key parenting skills can have far reaching effects on improving a diverse array of child outcomes. Further, these studies have shown that parenting skills can be taught; and they are malleable. Given these advances, prevention scientists are in a position to make solid empirically-based recommendations to public child service systems on using parent-mediated interventions to optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As parenting programs are scaled-up (Chamberlain, 2017; Haggerty, & Shapiro, 2013; Welsh, et al, 2016), providers need information to understand how different populations may respond to available interventions. This review summarizes the effectiveness of parent training programs in reducing substance use across gender, age/school grade, and race/ethnicity of youth participants.…”
Section: Resultsmentioning
confidence: 99%
“…As parenting programs are scaled-up (Chamberlain, 2017; Haggerty, & Shapiro, 2013; Welsh, et al, 2016), providers need information to understand how different populations may respond to available interventions. This review summarizes the effectiveness of parent training programs in reducing substance use across gender, age/school grade, and race/ethnicity of youth participants.…”
Section: Resultsmentioning
confidence: 99%
“…Use of research evidence was found in an earlier study to be significantly associated with the final stage achieved, as measured by the SIC, of TFCO by county-level youth-serving systems in California and Ohio ( 30 ). Engagement with other stakeholders both within the agency and external to the agency suggests that implementation is a “trans-relational” phenomenon involving interactions with other agencies ( 31 , 32 , 33 ), researchers ( 34 , 35 ), and intermediaries ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…They may also be better positioned to understand the context of public systems and propose policy or practice changes that enable public systems to adopt EBIs. For example, Chamberlain (2017) described how her purveyor organization worked with administrators of child welfare systems in New York and Tennessee to scale up two family-focused EBIs. The organization collaborated with the New York Administration for Children and Families (ACS) to have caseworkers implement the EBIs instead of referring parents to other organizations, which meant the purveyor also had to work with ACS to identify ways to reduce caseworkers’ workloads to accommodate this shift in responsibilities.…”
Section: Developer and Funder Capacity To Scale Up Ebismentioning
confidence: 99%